The deltares aqua monitor (2020)
Has the world become wetter or dryer? Can we see global trends in the changes of coastlines, and are these trends also apparent where we live? Is the total surface water storage on land growing or shrinking? These are rather simple questions, but have so far been hard to answer, and yet are important in order to understand the dynamics of our planet and the attribution of these dynamics to climate anomalies, and climate or man-made change. Answering these questions requires the availability of global maps at a very high resolution, which are very accurate and updated frequently. Remotely sensed Earth Observation (EO) data, such as satellite imagery, can obviously be used for this purpose. The volume of such data is increasing exponentially . To store, handle and analyse these data on a global scale requires a combination of access to enormous data storage and highperformance computers. It would require man-years working on the data preparation, exploring algorithms before the actual analysis, could be started. Until recently, such analyses could only be performed by highly specialized scientists and engineers, and on a case-by-case basis. The Deltares Aqua Monitor is a game changer showing that this situation is rapidly changing. It also shows that the way we analyse and use these data differs from what was common practice until very recently.